STUDY OF EFFECT, ACTION MECHANISM, AND SAFETY OF EXTRACT ETHANOL OF MANGOSTEEN (GARCINIA MANGOSTANA L.) RIND AS ANTIDIABETIC MELLITUS - Mahmudah, Rifa'atul
Mangosteen (Garcinia mangostana L.) rind is one of the traditional medicine that have antihyperglycemic effect. This material is easy to find in Indonesia and has been generally used by the community as traditional medicine. The compounds ?mangostin, ?-mangostin, and xanthones contained in the mangosteen rind were used as markers. This study aims to examine the effect, mechanism of action, safety profile, and establish quality standardization of the ethanol extract of mangosteen rind (EEKM). EEKM used in this research was obtained from PT. Borobudur and is an extract from maceration using 70% ethanol as a solvent with the addition of Maltodextrin as a filler. The research stages include testing the effect, mechanism of action, and safety of EEKM in silico and in vivo, as well as quality standardization of extracts and analysis of marker compound content (?-mangostin, ?-mangostin, and xanthone). Molecular docking study showed that ?-mangostin, ?-mangostin, and xanthone ligand could bind to the receptors/enzymes GLUT-4, PPAR-?, DPP-4, Aldose reductase, GLP-1, GSK-3?, GSK-3?, CD-4, and SGLT-2 indicated by the values of binding affinity which were comparable to those of the comparator ligands, drugs having the same target. Meanwhile, through molecular dynamic analysis of the SGLT-2 receptor, ?-mangostin showed higher stability compared to ?-mangostin and xanthone indicating its highest role in binding to the SGLT-2 receptor. In vivo test in rats induced with high-fat diet (HFD) and 35 mg/kg Streptozotocin showed that the administration of each dose of EEKM (100 mg/kg bw rat, 200 mg/kg bw rat, and 400 mg/kg bw rat) had glucose lowering effect with EEKM at 400 mg/kg bw rat as the most potent. Observation on the expression of the SGLT-2 gene in the kidneys through the RT-qPCR method showed significant differences (p<0.05) between the EEKM 200 and 400 mg/kg bw groups compared to the control group, and there was no significant difference against the Empagliflozin group. The animal blood serum was analyzed using the ELISA method and showed significant differences (p<0.05) in the increase in GLUT-4 between the control group (Na.CMC 0.3%) compared to the 200 and 400 mg/kg EEKM groups. Meanwhile the results of the analysis on the increase in PPAR-? and decrease in SGLT-2 showed significant differences(p<0.05) between the control group (Na.CMC 0.3%) compared to all EEKM groups (100, 200, 400 mg/kg bw). Similar results were also shown by the comparator drugs (Empagliflozin, Pioglitazone, and Metformin). Nevertheless, it can be concluded that EEKM at a certain dose can have an effect as antidiabetic mellitus through the mechanism of action of increasing the expression of GLUT-4 and PPAR-?, as well as decreasing the expression of SGLT2. The safety test using a virtual toxicity test, Protox-II Web Server predicted that ?mangostin with an LD50 of class 5, did not show any toxic effects on all test parameters (hepatotoxic, carcinogenic, immunotoxic, mutagenic, and cytotoxic). Therefore, is estimated that this compound is the safest compound in EEKM, compared to ?-mangostin and xanthone, which were only in class 4 toxicity and showed toxic effects on several organs. Furthermore, the chronic toxicity test for 6 months on the mangosteen (Garcinia mangostana L.) rind extract did not show any difference in the behavior and mortality of the test animals. In addition, EEKM at all test doses showed no significant difference compared to the control group (Na.CMC 0.3%), as well as between groups in terms of parameters of body weight, hematology, and organ weight. However, through biochemical observations, there was a significant difference (p<0.05) between the control group (Na.CMC 0.3%) compared to the EEKM group at doses of 200 and 400 mg/kg bw in the GOT parameters of male and female rats and triglycerides and creatinine upon administration of EEKM at 400 mg/kg body weight in male rats. This was also seen in histological observations, which showed liver abnormalities when EEKM was given at a dose of 200 mg/kg bw in female rats and 400 mg/kg bw in male and female rats. Organ abnormalities were also occurred in the histological observations of the male rat kidney given EEKM 400 mg/kg bw. Taken together, results of this study suggest that EEKM at a dose of 100 mg/kg bw is the the most suitable dose for long-term use (6 months). Based on the results of the extract quality analysis test, the EEKM used in the study was found to meet the standardization of specific and non-specific parameters. The extract contained alkaloids, flavonoids, saponins, tannins, and triterpenoids. The contents of markers ?-mangostin, ?-mangostin, and xanthone, determined by HPLC, were 19.88%, 16.15%, and 7.66%, respectively. Their Rf values and spectral of each compounds were almost similar to the components of EEKM, based on TLC-densitometry.